Investigating Properties of Concrete on Partially Replacing Cement by Wheat Straw Ash and Bamboo Wood Ash (International Journal of Innovative Research in Engineering & Management, 2023)
This study focuses on the recycling of  agricultural and industrial wastes, specifically wheat straw  ash (WSA) and bamboo wood ash (BWA), in cement  production to promote sustainable and environmentally friendly concrete. The mechanical properties of WSA and  BWA are investigated through tests measuring compressive  strength, flexural strength, and split tensile strength of  concrete. Different percentages of WSA and BWA (5%,  10%, 15%, and 20% by weight of cement) are used as  partially replacement materials in the concrete mix. The experimental results indicate a reduction in the strength  performance of concrete when WSA and BWA are  individually used as supplementary cementitious materials  at various curing periods (7, 28, 56, and 90 days). The  primary objective of this study is to examine the impact of  WSA and BWA on the mechanical properties of concrete  for the purpose of sustainable development. The heavy use of energy and raw materials in traditional  cement manufacture leads to a significant release of carbon  dioxide into the atmosphere, which contributes to  environmental pollution and greenhouse gas emissions. The  environmental impact of cement production can be  minimised by using WSA and BWA as cementitious  materials in concrete. This is a successful strategy for  reducing the damaging consequences of cement production  on the environmentWSA and BWA can be used as  cementitious materials in concrete to lessen the negative  environmental effects of cement manufacture. This is a  practical method for reducing the damaging environmental  effects of cement manufacture.
Keywords: Mechanical Properties; Wheat Straw Ash; Bamboo Wood Ash; Concrete; Sustainable Development